Themis Files : Sleeping Giants - Book 1 Book 1 - Neuvel, Sylvain, 1973- (New York : Del Rey, 2016)
"17 years ago: A girl in South Dakota falls through the earth, then wakes up dozens of feet below ground on the palm of what seems to be a giant metal hand. Today: She is a top-level physicist leading a team of people to understand exactly what that hand is, where it came from, and what it portends for humanity. A swift and spellbinding tale told almost exclusively through transcriptions of interviews conducted by a mysterious and unnamed character, this is a unique debut that describes a hunt for truth, power, and giant body parts"--
Keywords: Giants -- Fiction; Robots -- Fiction; Women physicists -- Fiction; Science Fiction